2021
DOI: 10.3389/fnins.2021.731292
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap Between Morphometric Similarity Mapping and Gene Transcription in Alzheimer’s Disease

Abstract: Disruptions in brain connectivity have been widely reported in Alzheimer’s disease (AD). Morphometric similarity (MS) mapping provides a new way of estimating structural connectivity by interregional correlation of T1WI- and DTI-derived parameters within individual brains. Here, we aimed to identify AD-related MS changing patterns and genes related to the changes and further explored the molecular and cellular mechanism underlying MS changes in AD. Both 3D-T1WI and DTI data of 106 AD patients and 106 well-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The finding that morphometric similarity networks are spatially co-located with transcriptional similarity or gene co-expression networks (Seidlitz et al, 2018) has spurred subsequent research efforts to link MRI-derived connectomes to underlying transcriptional patterns (Seidlitz et al, 2020; Morgan et al, 2019; Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that morphometric similarity networks are spatially co-located with transcriptional similarity or gene co-expression networks (Seidlitz et al, 2018) has spurred subsequent research efforts to link MRI-derived connectomes to underlying transcriptional patterns (Seidlitz et al, 2020; Morgan et al, 2019; Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…For example, by combining cortical transcriptomic data from the Allen Human Brain Atlas (Hawrylycz et al, 2015) with structural MRI from subjects with one of six different chromosomal copy number variation (CNV) disorders, Seidlitz et al (2020) demonstrated that the changes in morphometric similarity induced by each CNV closely resembled the spatial expression patterning of genes from the affected chromosome. Other studies have shown that changes in morphometric similarity in psychotic disorders (Morgan et al, 2019), major depressive disorder (Li et al, 2021), and Alzheimer’s disease (Zhang et al, 2021) correspond to the cortical expression of disease-relevant genes.…”
Section: Introductionmentioning
confidence: 99%
“…MS network analysis has been used to explore the correlation between brain structural changes and underlying transcriptomic signatures for various mental and neurological diseases. 22 , 23 , 24 , 25 However, this novel approach has not been applied to PD patients, particularly early drug‐naive PD patients, which could avoid the potential confounding influence of medication and disease duration.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we sought to investigate whether brain-wide AD-related gene expression correlates with regional variation in CBF. While prior investigations have determined associations between gene expression and MRI based markers of regional aging / AD – associated atrophy, this approach has not yet been considered for cerebrovascular architecture ( Groot et al, 2021 ; Vidal-Pineiro et al, 2020 ; Zhang et al, 2021 ). These analyses will establish the regional cortical co-expression of AD risk genes and AD-risk gene related CBF reductions, providing a plausible mechanistic link between AD risk loci and a well-established pathophysiological process in AD.…”
Section: Introductionmentioning
confidence: 99%